Recognizing composite entities in ordering chatbots - Đỗ, Thị Hương ([s. l.], 2020)
An overview of the chatbot system, the application potential of the chatbot ordering system, and an overview architecture for the chatbot ordering system simultaneously introduces the two main components in the model that this research discusses. The next section of the research deals with the proposed solution to the architecture mentioned by putting on the problem of identifying the composite entity. Presenting research related to building a chatbot ordering system. This is followed by surveys of methods for addressing the problem of recognizing composite entities from primitive methods to modern methods such as the use of neural networks. The final part is the presentation of the theoretical bases of some methods to solve the problem of chain labeling in general as well as identifying entities in particular through the use of the CRF model. Describe the proposed methods for solving a composite entity identification problem and a variant method for applying a special order domain data set. The research presents some experiments for the composite entity identification problem model.